Effects of Cytokines on Prognosis of Postoperative Complications in Children after Cardiopulmonary Bypass Surgery - L. V. Moshkivska; S. G. Khemio Arnes; O. Ya. Bespalova; E. A. Nastenko; O. K. Nosovets; A. S. Golovenko; V. V. Lazorishinetz (Ukrainian Journal of Cardiovascular Surgery, 2016)
The current work is dedicated to the analysis of cytokines effects on the prognosis of the severity and the amount of postoperative complications in children after cardiopulmonary bypass surgery (CPB). The frequency of complications was calculated and a direct correlation between the level of cytokines and the development of postoperative complications was established for patients undergoing cardiac surgery.